2022
DOI: 10.1155/2022/1698137
|View full text |Cite
|
Sign up to set email alerts
|

Feature Subset Selection with Optimal Adaptive Neuro-Fuzzy Systems for Bioinformatics Gene Expression Classification

Abstract: Recently, bioinformatics and computational biology-enabled applications such as gene expression analysis, cellular restoration, medical image processing, protein structure examination, and medical data classification utilize fuzzy systems in offering effective solutions and decisions. The latest developments of fuzzy systems with artificial intelligence techniques enable to design the effective microarray gene expression classification models. In this aspect, this study introduces a novel feature subset select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Furthermore, the study was not employed to binary classification that may achieved less accuracy. Hila et al [16] presented a novel feature subset selection technique for gene expression classification that makes use of an adaptive neuro-fuzzy inference system. Four independent microarray gene expression datasets-Leukemia, Prostate Cancer, DLBC Stanford, and Colon Cancer-each linked to a distinct type of cancer were used in the analysis to evaluate this methodology.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, the study was not employed to binary classification that may achieved less accuracy. Hila et al [16] presented a novel feature subset selection technique for gene expression classification that makes use of an adaptive neuro-fuzzy inference system. Four independent microarray gene expression datasets-Leukemia, Prostate Cancer, DLBC Stanford, and Colon Cancer-each linked to a distinct type of cancer were used in the analysis to evaluate this methodology.…”
Section: Related Workmentioning
confidence: 99%
“…Hilal et al [9], suggested a novel feature subset selection with an optimum adaptive neuro-fuzzy inference system (FSS-OANFIS) for cancer classification. The colon cancer dataset produced the best results, with 89.47%, 87.80%, 87.82%, and 87.82% for accuracy, sensitivity, specificity, and G-measure, respectively.…”
Section: Related Workmentioning
confidence: 99%